Khiṭāb ‘Ilm Al-Nafs Al-Ṣūfī: Tatabbu' Al-Judhūr Wa Al-Naẓariyyāt Wa Al-Taṭbīqāt - Rizqa Ahmadi; Abad Badruzaman (Refleksi: Jurnal Kajian Agama dan Filsafat, 2021)
Sufi Psychology studies continue to be explored for the sake of scientific independence. The inhibiting factor of this study is the differences in terms of paradigmatic characters of the two disciplines. The Psychology that tends towards empirical-positivism is different from Sufism which tends to be subjective-personal. However, this fact did not reduce the efforts of the scholars to build a bridge between of the two. Recent psychology studies have placed spirituality as an important element so that the Transpersonal Psychology and Humanistic Psychology schools emerged. Likewise, contemporary Sufism studies are increasingly contextual to various socio-cultural problems and are not limited to the study of the doctrines and teachings of rigorous Sufi orders. Through a literature review that is presented descriptively with a historical-thematic approach, this paper presents Sufi Psychology as a synthesis between the two disciplines. Substantially, Sufi psychology has existed in early Islamic tradition. The nature of Sufi psychology is also scattered in the Sufi tradition that developed in the 3rd and 4th centuries of Hijriyah. As for the epistemic formula, the term Sufi Psychology can be found in the studies of Javad Nur Bakhsy, Robert Frager, Amir Najjar, and Lynn Wilcox. The theme of heart, self, and soul is the main topic of this study. In practical terms, theories of Sufi Psychology can complement findings that have not been widely disclosed in psychology, especially regarding psychiatric symptoms that are observed not only from behavioral assessments, as well as their relationship to transcendent elements.